Restructuring of a Municipal Company - Krzysztof WASOWICZ (Communications of International Proceedings, 2020)
This elaboration is to present the management process (restructuring) of a municipal collective transport company in a crisis situation. The theoretical purpose of this article is to depict the key issues regarding restructuring of municipal local collective transport companies. As the methodical goal, presentation of the restructuring process in a public transport company has been deemed. The empirical analysis of the restructuring process based on a specific company was replaced with an original decision-making game that formulated exemplary goals in individual areas of functioning of the enterprise. To enrich the cognitive value, the article includes many diagrams.
Keywords: municipal enterprise; restructuring; municipal collective transport company